Issues in Devanagari Ancient Character Recognition: A Study: Challenges and techniques for recognizing ancient handwritten Devanagari manuscripts (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A number of OCRs have been developed for the identification of fine printed Devanagari text. Some work has been done on recognition of handwritten Devanagari text. However very little work has been done in recognition of text for ancient handwritten Devanagari manuscripts. These manuscripts are very old and in delicate condition. These are not easily accessible. Ordinarily used techniques for handwritten recognition can't be applied directly to the ancient manuscripts as ancient manuscripts have unique characteristics. In this paper, these characteristics and different problems encountered while designing OCR for ancient handwritten Devanagari manuscripts have been identified.